The application of group consensus theory to aid organisational learning and sustainable innovation in manufacturing SMEs - Andrew Thomas; Peter Dorrington; Claire Haven-Tang; Rachel Mason-Jones; Mark Francis; Ron Fisher (Cogent Business & Management, 2018)
This paper investigates the exploring of situated knowledge within manufacturing organisations, with employees from a four-tier supply chain utilising a form of Group Consensus Theory (GCT). The implementation of GCT through focus groups as well as individual interviews with participants and observation of group dynamics allowed the authors to characterise the dynamics of learning and application of innovation projects and, identifies the types of innovation strategies in relation to organisational dynamics and knowledge. The aim of the work is to identify the underpinning issues relating to organisational dynamics and organisational learning in relation to innovation. Direct feedback from the SMEs will inform the analysis of how and in what way manufacturers can meet the challenge of increasing the attitudes towards improving innovative activities in companies. This paper extends the theoretical development around organisational learning towards understanding how companies within supply chains learn and innovate. This work therefore focuses upon inter-company learning and innovation which is largely under-developed from a research viewpoint. The method developed is practical, and may be used by organisations for themselves to aid the development of group as well as individual reflection, to stimulate the consideration of change. The results suggest that a clear connection exists between how companies are managed and led and, the resulting organisational learning capabilities of the collaborative team.
Keywords: 650